Learning from Baby P: the politics of blame, fear and denial - Shoesmith, Sharon (Jessica Kingsley Publishers, 2016)
Introduction -- The background to the familial homicide of Peter Connelly -- The denial of crimes against children -- Exploring processes of blame, fear and denial from a psychosocial perspective -- The socio-political and cultural context of the death of Peter Connelly -- The narrative about Baby P emerges -- The identification of a cultural trope that blames social workers for harm to children -- Conclusions and main findings